Synthesis of a phosphaphenanthrene/benzimidazole-based curing agent and its application in flame-retardant epoxy resin - Huo, Siqi; Liu, Zhitian; Li, Chuan; Wang, Xiaolei; Cai, Haopeng; Wang, Jun (Polymer degradation and stability, 2019)
A flame-retardant curing agent (DTA) for epoxy resin (EP), which was constructed by phosphaphenanthrene and benzimidazole groups, was successfully synthesized via one-pot reaction between 2-aminobenzimidazole, terephthalaldehyde, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO). DTA induced the decomposition of EP matrix and promoted the carbonization at high temperature. As expected, DTA endowed EP thermoset with excellent flame retardancy and smoke suppression. For instance, EP/DDS/DTA-0.5 sample containing only 0.5 wt% phosphorus passed UL94 V-1 rating and its LOI value increased to 34.2%. In addition, the pk-HRR, av-HRR, THR, TSR, and TSP of EP/DDS/DTA-1.0 sample were decreased by 56.6%, 31.6%, 34.4%, 24.6% and 24.6% in comparison to those of EP/DDS sample. The flame retardant mechanism showed that the decomposition products of DTA played an important role in the formation of a compact and intumescent char layer in condensed phase. Meanwhile, the phosphorus-containing and nitrogen-containing fragments, which was generated by the pyrolysis of DTA, quenched the active free radicals and diluted the fuels in gaseous phase. Therefore, DTA exerted flame retardant effect in condensed and gaseous phases during combustion. •A phosphaphenanthrene/benzimidazole-containing curing agent (DTA) was synthesized.•EP/DDS/DTA sample exhibited excellent flame retardancy.•DTA exerted flame-retardant effect in condensed and gaseous phases.